Stereoisomers of an Aryl Pyrazole Glucocorticoid Receptor Agonist Scaffold Elicit Differing Anti-inflammatory Responses - Lato, Ashley M.; Burke, Susan J.; Ducote, Maggie P.; Kennedy, Brandon J.; Collier, J. Jason; Campagna, Shawn R. (ACS medicinal chemistry letters, 2022)
Glucocorticoids (GCs) are heavily prescribed to control inflammation in various human diseases; however, side effects associated with GCs are well documented and lead to serious metabolic and immunological complications with long-term use. The paradigm for GC function includes two well described modes of activity: dimer formation of the glucocorticoid receptor (GR) promotes transactivation, while monomeric interaction with co-regulators promotes transrepression. Previously, a set of aryl pyrazole-derived glucocorticoid receptor agonists (APGRAs) with potency rivaling current commercially available glucocorticoids were described. In this study, a further series of existing and novel stereopure APGRAs were thoroughly examined for biological activity and evaluated for structure-activity relationships (SARs). The si isomers with an upward OH moiety were similar to 70% more active on average than the re isomers. Additionally, AP13 was found to elicit 79% transrepression of dexamethasone while eliciting less than half the transactivation response in 832/13 cells, a rat insulinoma cell line.